ENTREPRENEURIAL BEHAVIOR OF INTERNET KIOSK OWNERS OPERATING IN THE INFORMAL ECONOMY IN A BRAZILIAN SLUM: THE CASE OF ROCINHA IN RIO DE JANEIRO, BRAZIL - Moraes, Joysi; Mariano, Sandra R.H.; Medeiros, Silvio (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
The aim of this article is to investigate the characteristics, behaviors, motivations to start a business and the managerial practice of entrepreneurs, owners of internet kiosks, operating in the context of the informal economy in Rocinha, the biggest slum in Brazil, where 90.9% of businesses are informal. The Thematic Apperception Test used by McClelland serves the purpose of this research. The instrument used in this survey was adapted for Brazil. From the 92 internet kiosk entrepreneurs in Rocinha, 44 responded to the TAT questionnaire. Data were analyzed using SPSS 16.0. The analysis suggests that the behavior of the entrepreneurs in Rocinha match the entrepreneurial characteristics proposed by McClelland and their main motivations are seeking opportunities and increasing income and try to meet customers‟ needs and have a low perception of service differentiation.